Perancangan Cd Katalog Untuk Penyampaian Layanan Informasi Berbasis Multimedia Pada Rumah Sakit Persahabatan - Legowo, Nilo; Yosanny, Agustinna; Prabowo, Bagus (Bina Nusantara University, 2010)
CD katalog developed is an effort to improve service quality and effectiveness of delivering information to visitors Persahabatan Hospital. The method used is the method of literature, methods of analysis and design methods. Methods Literatur include the study of literature references relating to problems and applications. Methods include analysis of field studies with a survey on the current system as well as an analysis of surveys, interviews, and questionnaire distribution. The design method includes designing the menu structure, State Transition diagrams, screen design, database use, and module specifications. The results obtained in the form of multimedia CD-based catalog that presents the completeness of the information, such as facilities Persahabatan Hospital, clinic, the site plan, and schedule a doctor. The conclusion was based on a multimedia CD Catalog can be a new alternative as a medium to facilitate the search for location information and profile hospital. With the CD catalog is expected to visitors and prospective participants can find information about the Friendship Hospital, more easily, and help the Friendship Hospital in providing information to visitors Hospitals.